Equilateral Triangular Dielectric Resonator Nantenna at Optical Frequencies for Energy Harvesting - Waleed Tariq Sethi; Hamsakutty Vettikalladi; Habib Fathallah; Mohamed Himdi (International Journal of Antennas and Propagation)
The last decade has witnessed a remarkable growth in the telecommunication industry. With the introduction of smart gadgets, the demand for high data rate and bandwidth for wireless applications have increased exponentially at the cost of exponential consumption of energy. The latter is pushing the research and industry communities to devise green communication solutions that require the design of energy saving devices and techniques in one part and ambient energy harvesting techniques in the other part. With the advent of nanocomponents fabrication technology, researchers are now able to tap into the THz frequency regime and fabricate optical low profile antennas at a nanoscale. Optical antennas have proved their potential and are revolutionizing a class of novel optical detectors, interconnectors, sensors, and energy harvesting related fields. Authors in this paper propose an equilateral triangular dielectric resonator nantenna (ETDRNA) working at 193.5 THz standard optical frequency. The simulated antenna achieves an impedance bandwidth from 192.3 THz to 197.3 THz with an end-fire directivity of 8.6 dBi, covering the entire standard optical window of C-band. Numerical demonstrations prove the efficiency of the nantenna at the frequencies of interest, making it a viable candidate for future green energy harvesting and high speed optical applications.